2021
DOI: 10.1186/s13068-021-01904-2
|View full text |Cite
|
Sign up to set email alerts
|

THF co-solvent pretreatment prevents lignin redeposition from interfering with enzymes yielding prolonged cellulase activity

Abstract: Background Conventional aqueous dilute sulfuric acid (DSA) pretreatment of lignocellulosic biomass facilitates hemicellulose solubilization and can improve subsequent enzymatic digestibility of cellulose to fermentable glucose. However, much of the lignin after DSA pretreatment either remains intact within the cell wall or readily redeposits back onto the biomass surface. This redeposited lignin has been shown to reduce enzyme activity and contribute to rapid enzyme deactivation, thus, necessit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…prevent lignin redeposition onto the biomass surface and prolong cellulases activity (Patri et al, 2021). Microscopic analysis showed that after autohydrolysis pretreatment, lignin from Eucalyptus globulus migrates out of the cell wall and redeposits in certain regions of the fibers to form droplet-like structures.…”
Section: Lignin's Physical Barrier Propertiesmentioning
confidence: 99%
“…prevent lignin redeposition onto the biomass surface and prolong cellulases activity (Patri et al, 2021). Microscopic analysis showed that after autohydrolysis pretreatment, lignin from Eucalyptus globulus migrates out of the cell wall and redeposits in certain regions of the fibers to form droplet-like structures.…”
Section: Lignin's Physical Barrier Propertiesmentioning
confidence: 99%
“…3 ). Interestingly, a recent work on lignocellulosic fractionation pretreatment using tetrahydrofuran–water co-solvent revealed that the lignin globules deposited on the cellulose surface did not adsorb as much enzyme as lignin in the lignin–carbohydrate complex [ 9 , 39 ]. In other words, the deposited lignin merely provided an exterior physical obstacle on fiber surface, rather than strong adsorbents to cellulase enzymes [ 40 ], which allowed access of enzymes to cellulose with high-efficiency hydrolytic performance [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Results confirmed the aggravated exterior lignin coverage caused by 2-naphthol addition in acid EOS treatment, which in turn proved the greater fluidity of the less repolymerized lignin that modified by 2-naphthol. As discussed above, the lignin deposition on fiber surface probably cancelled out the negative effects of residual bulk lignin in the lignin–carbohydrate complex by reducing the unproductive binding, which turned out to be beneficial to enzymatic hydrolysis [ 9 , 40 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the removal of hemicellulose and lignin plays a significant role in obtaining higher conversion of carbohydrates from CELF-pretreated solids, the actual impact of residual lignin on the action of enzyme is yet to be explored. In view of that, Patri et al [62] developed co-solvent-enhanced lignocellulosic fractionation (CELF) method in order to solubilize lignin and to decrease the limitations associated with acid pretreatment. It was observed that with an incubation period of 5 weeks and enzyme doses of 2 mg protein/g, an enzymatic hydrolysis of CELF-pretreated switchgrass at 7.5% (w/w) of solid loadings attributes towards glucan to glucose yield of more than 90%.…”
Section: Advancement In the Processes To Overcome The Interference Ef...mentioning
confidence: 99%